2011
DOI: 10.1002/hfm.20287
|View full text |Cite
|
Sign up to set email alerts
|

Medication review software to improve the accuracy of outpatient medication histories: protocol for a randomized controlled trial

Abstract: Medication-prescribing errors generated at interfaces-in-care are the most common cause of preventable health care errors and contribute substantially to adverse patient outcomes. For this reason, standardized medication reconciliation (MR) processes need to be inserted at these interfaces. However, MR is an inherently complex task, and little data exist to inform system-based operationalization. The Portland Informatics Center addressed this challenge by creating an electronic patient-directed multimedia surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…52 In our adaptation of the framework, MR is a cyclical macroprocess composed of linked subprocesses (e.g., history collection, data adjudication, discrepancy resolution). 53 The quality of MR can only be as effective as the initial history. 35,53 We therefore designed our intervention to address system constructs supporting history collection.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…52 In our adaptation of the framework, MR is a cyclical macroprocess composed of linked subprocesses (e.g., history collection, data adjudication, discrepancy resolution). 53 The quality of MR can only be as effective as the initial history. 35,53 We therefore designed our intervention to address system constructs supporting history collection.…”
Section: Theorymentioning
confidence: 99%
“…53 The quality of MR can only be as effective as the initial history. 35,53 We therefore designed our intervention to address system constructs supporting history collection. 23,[52][53][54] The PSE contends that humans encode, store, and retrieve images from memory more easily than text or auditory information.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Potential ADEs are medication errors that have the potential to cause harm, but were intercepted by pharmacist's intervention or before reaching the patient [16,17]. Our events were assigned probability of harm scores which were adapted from other studies [3,7,[18][19][20] with few modifications and ranged from 0.1 to 1. A probability of harm score of 1 was given to an actual ADE identified and intercepted by the clinical pharmacist [3,7].…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled trial is ongoing to assess the accuracy of this software in comparison to a gold standard [70]. Schnipper et al [22,23,71] reported that patients using a medication module embedded in the Patient Gateway, an online patient health record, had fewer potentially harmful discrepancies.…”
Section: Comparison With Prior Workmentioning
confidence: 99%